2009
DOI: 10.1194/jlr.m800553-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The thyromimetic T-0681 protects from atherosclerosis

Abstract: This report describes studies in hyperlipidemic New Zealand White (NZW) rabbits investigating the impact of the liver-selective thyromimetic T-0681 on lipoprotein metabolism and the development of atherosclerosis. Prolonged treatment with T-0681 increased the hepatic expression of both LDL receptor and scavenger receptor class B, type I without affecting cholesteryl ester transfer protein activity. Upregulation of hepatic lipoprotein receptors was accompanied by a marked decrease of apolipoprotein B-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
(41 reference statements)
3
25
1
Order By: Relevance
“…In agreement with this reasoning, evidence of reduced atherosclerosis in animal models such as cholesterolfed rabbits [20 ] and apoE-knockout mice [19 ] has now been reported using the liver-selective thyromimetic T-0681.…”
Section: Thyroid Hormone Mimetics For Lipid Modulation and Atherosclementioning
confidence: 71%
“…In agreement with this reasoning, evidence of reduced atherosclerosis in animal models such as cholesterolfed rabbits [20 ] and apoE-knockout mice [19 ] has now been reported using the liver-selective thyromimetic T-0681.…”
Section: Thyroid Hormone Mimetics For Lipid Modulation and Atherosclementioning
confidence: 71%
“…The liver selective TR agonist T-0681, sodium;3-[4-[3-[(4-fluorophenyl)-hydroxymethyl]-4-hydroxyphenoxy]-3,5-dimethylanilino]-3-oxopropanoate (also known as KAT-681), has recently been demonstrated to have beneficial effects on atherosclerotic lesions in cholesterolfed rabbits and mice deficient in apolipoprotein E Tancevski et al, 2009). T-0681 induced the LDL and HDL receptors in rodents and in addition was found to significantly increase fecal excretion of macrophage-derived neutral and acidic sterols (Tancevski et al, 2010).…”
Section: Selective Thyroid Hormone Receptor Modulatorsmentioning
confidence: 99%
“…Recently, it has been shown that liver-selective thyromimetics upregulate hepatic SR-BI, which is an important component in reverse cholesterol transport (RCT) [7], [10]. By their dual action on LDL metabolism and RCT, thyromimetics could be expected to counteract atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%